The Correlation Between Diet Patterns and Anemia on Female Adolescent at Madarasah Aliyah Negeri 1 Sleman - Wahyuntari, Evi; Indahsari, Sulistyaning Nur (Jurnal Kesehatan Cendikia Jenius, 2024)
Anemia is a condition where the number of red blood cells or hemoglobin (Hb) levels in the blood is lower than normal values ​​for groups of people according to age and gender. Based on data from the DIY Provincial Health Service in 2023, the number of anemic teenagers will reach 29.5%. This study aims to determine the relationship between diet and the incidence of anemia in young women at Madrasah Aliyah Negeri 1 Sleman. This type of research uses analytical observational, with a cross-sectional approach. The sampling technique used in this research was a purposive sampling technique, namely 45 samples. Data collection tools and methods use questionnaires and digital Hb check tools. This research was conducted in June 2024. The majority of teenagers aged 15-17 years at Madrasah Aliyah Negeri 1 Sleman who had poor diets were 19 respondents (42.2%) while 31 young women aged 15-17 years had anemia. respondents (68.9%) at Madrasah Aliyah Negeri 1 Sleman. The results of statistical tests using chi-square obtained a p-value <0.05, namely 0.000, so it can be concluded that Ha is accepted, meaning that the hypothesis in this research is that there is a relationship between the independent variable and the dependent variable. variable. It is recommended that young women be encouraged to prevent anemia and improve their diet to include nutritious nutrition.